Implikasi Profitabilitas Terhadap Nilai Perusahaan dan Kebijakan Dividen Sebagai Variabel Intervening (Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2009-2016) - Hairudin Hairudin; Umar Bakti; Agung Rachmadi (Jurnal Manajemen dan Bisnis, 2020)
This research examines and discovers the implication of profitability on firm value, and dividend policy as mediating effect at mining companies which are listed on Indonesian Stock Exchange in 2009-2016 with total samples, 5 companies. This study using path analysis to solve the problem with the help of SPSS 24. The result shows that Profitability and dividend policy have positive effect and significant on firm value, Profitability has negative effect on dividend policy, and dividend policy has no mediating effect between profitability and firm value.